Distinct Mechanisms for Visual and Motor-Related Astrocyte Responses in Mouse Visual Cortex - Slezak, Michal (Curr Biol, 2019)
Astrocytes are a major cell type in the mammalian nervous system, are in close proximity to neurons, and show rich Ca(2+) activity thought to mediate cellular outputs. Astrocytes show activity linked to sensory [1, 2] and motor [3, 4] events, reflecting local neural activity and brain-wide neuromodulatory inputs. Sensory responses are highly variable [5, 6, 7, 8, 9, 10], which may reflect interactions between distinct input types [6, 7, 9]. However, the diversity of inputs generating astrocyte activity, particularly during sensory stimulation and behavior, is not fully understood [11, 12]. Using a combination of Ca(2+) imaging, a treadmill assay, and visual stimulation, we examined the properties of astrocyte activity in mouse visual cortex associated with motor or sensory events. Consistent with previous work, motor activity activated astrocytes across the cortex with little specificity, reflecting a diffuse neuromodulatory mechanism. In contrast, moving visual stimuli generated specific activity patterns that reflected the stimulus' trajectory within the visual field, precisely as one would predict if astrocytes reported local neural activity. Visual responses depended strongly on behavioral state, with astrocytes showing high amplitude Ca(2+) transients during locomotion and little activity during stillness. Furthermore, the amplitudes of visual responses were highly correlated with pupil size, suggesting a role of arousal. Interestingly, while depletion of cortical noradrenaline abolished locomotor responses, visual responses were only reduced in amplitude and their spatiotemporal organization remained intact, suggesting two distinct types of inputs underlie visual responses. We conclude that cortical astrocytes integrate local sensory information and behavioral state, suggesting a role in information processing.